Intraoperative determination of the adequacy of myotomy length during peroral endoscopic myotomy (POEM): the double-endoscope transillumination for extent confirmation technique (DETECT) - Khashab, Mouen A.; Kumbhari, Vivek; Azola, Alba; Zein, Mohamad El; Messallam, Ahmed A.; Abdelgelil, Ahmed; Besharati, Sepideh; Kalloo, Anthony N.; Saxena, Payal (Endoscopy, 2015)
Background and study aims: Precise identification of the gastroesophageal junction (GEJ) is a challenging prerequisite for adequate length of an esophageal myotomy. Multiple standard methods to identify the GEJ have been described; however, a more objective modality is needed to ensure effective peroral endoscopic myotomy (POEM).Patients and methods: In the double-endoscope transillumination for extent confirmation technique (DETECT), an ultraslim gastroscope is passed to the most distal aspect of the submucosal tunnel created during POEM. A regular gastroscope is advanced into the stomach, and the visualization of transillumination from the ultraslim gastroscope enables identification of the extent of the submucosal tunnel.Results: A total of 10 patients underwent POEM with DETECT. Initial submucosal tunneling was performed based on a determination of the GEJ location via standard methods. DETECT indicated the tunnel extent to be inadequate in 50 % of patients, and the tunnel was extended a further 1 to 2 cm. The mean initial tunnel length was 15.4 cm, with a mean initial myotomy length of 11.9 cm. DETECT was performed in less than 10 minutes without complications.Conclusion: DETECT is an objective method for determining the adequacy of the submucosal tunnel length during POEM.